Dynamic immune and molecular responses to chronic heat stress in blood and peripheral blood mononuclear cells of dairy cows - Koch, Franziska; Viergutz, Torsten; Kühn, Christa; Kuhla, Björn (Frontiers in Immunology, 2025)
BackgroundAs a result of climate change, dairy cows even in confinement systems are exposed to high ambient temperatures and environmental factors inducing heat stress. However, there are indications that chronic heat stress with reduced feed intake initially stimulates a systemic inflammatory response and progressively reduces the immunocompetence. This finally increases the disease susceptibility. This study aimed to elucidate the effects of chronic heat stress or equivalent reduced feed intake via pair-feeding at thermoneutrality on the daily hematological profile, leukocyte NF-κB p65 signaling pathway, immune function, and metabolism in peripheral blood mononuclear cells (PBMC) of dairy cows. MethodsPrimiparous, mid-lactating Holstein cows (n = 30) were assigned to heat-stressed (HS; temperature-humidity index (THI) 76, 28°C, relative humidity (RH) 50%), control (CON; THI 60, 16°C, RH 69%), or pair-fed (PF; THI 60, 16°C, RH 69%) group for 7 days. ResultsHS cows showed a lower number of erythrocytes, platelets, lymphocytes, hemoglobin, hematocrit, and iron concentration and increased endotoxin concentration compared to PF cows. The presence of NF-κB p65 in the nucleus of leukocytes was lower in HS than in the two other groups on day 5, while it was higher in HS cows on day 6. Furthermore, on day 6, RNA sequencing of PBMC showed an enrichment of higher expressed genes in pathways of platelet activation, coagulation cascade, leukocyte transendothelial migration, and focal adhesion in HS cows compared to both non-heat-stressed groups. However, T cell receptor signaling pathway, intestinal immune network for IgA production, antigen processing and presentation, and metabolic processes were expressed lower in HS compared to CON cows. ConclusionThe results suggest that heat stress induces dynamic changes of the red blood cell and lymphocyte profiles but only transiently activating the leukocytic NF-κB p65 signaling pathway while suppressing T cell signaling, both likely in response to the increased circulating endotoxin concentration. The activation of platelets and the coagulation cascade were likely due to heat-stress-induced microvascular injuries, altered hematocrit, or vasodilatation. Altered blood coagulation and immune responses need to be considered in the management of heat-stressed dairy cows.